Developing context sensitive approaches to change: contextual features - Hailey, Veronica Hope (Henry Stewart Talks, 2009)
The process of delivering strategic change, Diagnosing context, The change kaleidoscope, Contextual features, Time, Scope, Preservation, Diversity -Capability, Capacity, Readiness, Power